(untitled) (Med Phoenix, 2020)
Background: Anaemia in pregnancy is a global health challenge. It is the commonest medical disorder of pregnancy and a major cause of morbidity and mortality in developing countries. Main cause of anaemia in obstetrics is iron deficiency. There are specific risks for the mother and the fetus such as intrauterine growth retardation, prematurity, and blood transfusion. Hence, the importance of giving iron in the antenatal period and to be continued postnatally. Objectives: The study was conducted to determine the overall prevalence of anaemia among pregnant women presenting in third trimester and its effect on pregnancy outcome. Methods: This is a cross sectional descriptive study done at National Medical College & Teaching Hospital from September 2015 to August 2016. During the study period 2048 pregnant women attended antenatal clinic in third trimester. Among 2048, 1200 were booked cases and out of these women with haemoglobin less than 11gm/dl were labeled as anaemia. The prevalence was calculated along with the maternal and fetal outcome. Result: Among 2048, 1200 were booked cases, 368 (30.66%) were anemic, 66.30% were multigravida, 67.93% in age group of 21-30 years, 284 patients came for delivery. In 14.08% patients there was preterm labour, apgar score less than 7 in 66.19% babies. Majority of neonate weighed between 2.0 - 2.5kg (49.29%). Perinatal deaths were 2.81%. Conclusion: Anaemia in pregnancy need awareness about early and regular antenatal care with oral iron supplementation. Correction of anaemia will reduce the maternal and fetal complications.